Against the View that Consciousness and Attention are Fully Dissociable - Marchetti, Giorgio (Frontiers in Psychology, 2012)
In this paper, I will try to show that the idea that there can be consciousness without some form of attention, and high-level top-down attention without consciousness, originates from a failure to notice the varieties of forms that top-down attention and consciousness can assume. I will present evidence that: there are various forms of attention and consciousness; not all forms of attention produce the same kind of consciousness; not all forms of consciousness are produced by the same kind of attention; there can be low-level attention (or preliminary attention), whether of an endogenous or exogenous kind, without consciousness; attention cannot be considered the same thing as consciousness.